Microwave-assisted biosynthesis of flower-shaped ZnO for photocatalyst in 4-nitrophenol degradation - Sulistyo Rini, Ari; Aji, Arie Purnomo; Rati, Yolanda (Communications in Science and Technology, 2022)
In this paper, the flower-shaped ZnO particles have been prepared via microwave-assisted biosynthesis technique using an aqueous extract of Sandoricum koetjape peel at various irradiation powers, i.e. 180, 360, 540, and 720 Watt. The synthesized flower-shaped ZnO particles were characterized using UV-Vis spectroscopy, x-ray diffraction (XRD), and field emission scanning electron microscope (FESEM). The UV-vis spectra exhibited ZnO absorption peaks in the UV region with band gap energy in the range of 3.25 - 3.29 eV. XRD analysis confirmed the hexagonal wurtzite crystal with the high purity of ZnO particles. The flower-shaped morphology of ZnO was evident in FESEM images with the decrease of particle diameter as the radiation power increased from 257 to 447 nm. ZnO prepared at 720 Watt (Z-720) succeeded in degrading 4-nitrophenol with the highest efficiency of 84.8 % after 240 min. Consequently, biosynthesis ZnO will have a great opportunity to be applied in degrading wastewater pollutants.